Night-shift work increases morbidity of breast cancer and all-cause mortality: a meta-analysis of 16 prospective cohort studies - Lin, Xiaoti; Chen, Weiyu; Wei, Fengqin; Ying, Mingang; Wei, Weidong; Xie, Xiaoming (Sleep medicine, 2015)
•This meta-analysis included 16 prospective cohort studies.•A positive dose–effect relationship was found between night-shift work and incident breast tumors.•Rotating night-shift work enhances morbidity of breast cancer by 8.9%.•Night-shift work is associated with a 2.7% increase in cardiovascular death. Night-shift work (NSW) has previously been related to incidents of breast cancer and all-cause mortality, but many published studies have reported inconclusive results. The aim of the present study was to quantify a potential dose–effect relationship between NSW and morbidity of breast cancer, and to evaluate the association between NSW and risk of all-cause mortality. The outcomes included NSW, morbidity of breast cancer, cardiovascular mortality, cancer-related mortality, and all-cause mortality. Sixteen investigations were included, involving 2,020,641 participants, 10,004 incident breast cancer cases, 7185 cancer-related deaths, 4820 cardiovascular end points, and 2480 all-cause mortalities. The summary risk ratio (RR) of incident breast cancer for an increase of NSW was 1.057 [95% confidence interval (CI) 1.014–1.102; test for heterogeneity p = 0.358, I2 = 9.2%]. The combined RR (95% CI) of breast cancer risk for NSW vs daytime work was: 1.029 (0.969–1.093) in the <5-year subgroup, 1.019 (1.001–1.038) for 5-year incremental risk, 1.025 (1.006–1.044) for 5- to 10-year exposure times, 1.074 (1.010–1.142) in the 10- to 20-year subgroup, and 1.088 (1.012–1.169) for >20-year exposure lengths. The overall RR was 1.089 (95% CI 1.016–1.166) in a fixed-effects model (test for heterogeneity p = 0.838, I2 = 0%) comparing rotating NSW and day work. Night-shift work was associated with an increased risk of cardiovascular death (RR 1.027, 95% CI 1.001–1.053), and all-cause death 1.253 (95% CI 0.786–1.997). In summary, NSW increased the risk of breast cancer morbidity by: 1.9% for 5 years, 2.5% for 5–10 years, 7.4% for 10–20 years, and 8.8% for >20-years of NSW. Additionally, rotating NSW enhanced the morbidity of breast cancer by 8.9%. Moreover, NSW was associated with a 2.7% increase in cardiovascular death.